Staples for Intra-Operative Skin Retraction in Hand Surgery - O’Neill, J.K.; Robinson, P.; Giddins, G.E.B. (Journal of Hand and Microsurgery, 2014)
In certain situations staples are a quick and effective method of retracting the skin to give access to the operative site. Staples, once placed, are more reliable and predictable than an assistant with a skin hook. Furthermore, their use frees up the assistant to perform other tasks including further deeper tissue retraction. Staples pinch the skin rather than piercing it and this is especially of value in patients on steroid treatment or with thin skin that may bruise easily. They leave no discernible marks on removal.
Keywords: Hand; Retraction; Staples; Skin hook